Effects of long-term childhood exercise and detraining on lipid accumulation in metabolic-related organs. - Son Tien Nguyen; Naoto Fujita; Takaya Oshima; Misuzu Nishihira; Haruya Ohno; Masayasu Yoneda; Susumu Urakawa (PLoS ONE, 2022)
The preventive effects of regular exercise on obesity-related health problems are carried over to the non-exercise detraining period, even when physical activity decreases with aging. However, it remains unknown whether regular childhood exercises can be carried over to adulthood. Therefore, this study aimed to investigate the effects of long-term childhood exercise and detraining on lipid accumulation in organs to prevent obesity in adulthood. Four-week-old male Otsuka Long-Evans Tokushima Fatty (OLETF) rats were used as obese animals. OLETF rats were allocated into sedentary and exercise groups: exercise from 4- to 12-week-old and detraining from 12- to 20-week-old. At 12-week-old immediately after the exercise period, regular exercise completely inhibited hyperphagia, obesity, enlarged pancreatic islets, lipid accumulation and lobular inflammation in the liver, hypertrophied adipocytes in the white adipose tissue (WAT), and brown adipose tissue (BAT) whitening in OLETF rats. Additionally, exercise attenuated the decrease in the ratio of muscle wet weight to body weight associated with obesity. Decreased food consumption was maintained during the detraining period, which inhibited obesity and diabetes at 20-week-old after the detraining period. Histologically, childhood exercise inhibited the enlargement of pancreatic islets after the detraining period. In addition, inhibition of lipid accumulation was completely maintained in the WAT and BAT after the detraining period. However, the effectiveness was only partially successful in lipid accumulation and inflammation in the liver. The ratio of muscle wet weight to body weight was maintained after detraining. In conclusion, early long-term regular exercise effectively prevents obesity and diabetes in childhood, and its effectiveness can be tracked later in life. The present study suggests the importance of exercise during childhood and adolescence to inhibit hyperphagia-induced lipid accumulation in metabolic-related organs in adulthood despite exercise cessation.